Використання технологій в економіці України: практичні аспекти теорії флуктуацій - Почерніна, Наталя Вікторівна; Pochernina, Natalia (К.: НУХТ, 2022)
UK: В статті на основі проведеного аналізу були виявлені кількісні та структурні флуктуації в технологічній сфері України за критерієм ефективності зайнятості у розрізі спеціальних агрегацій різного рівня використання технологій. Методика ґрунтувалась на розрахунку ступеня дисбалансу технологічної структури національної економіки та індексу Тейла для сфери виробництва та сфери послуг на основі показника доданої вартості на одного зайнятого. Для зменшення негативних ефектів виявлених флуктуацій та підсилення здатності технологічної сфери до самоорганізації запропонована система заходів економічної політики з урахуванням цільової направленості розвитку економіки у напрямку цифровізації. Акцентована увага, що в контексті підвищення ефективності використання ресурсу праці цифровізація дає широкий спектр можливостей як для підвищення рівня зайнятості, так і для підвищення освітньо-кваліфікаційного рівня працівників та розвитку культури комунікацій між громадянами, бізнесом та державою. //// EN:The purpose of this article is to analyze the dynamics of technology use in the Ukrainian economy during 2013-2020 in order to identify fluctuations that determine the vector of development of the country's technological sphere in the context of its ability to self-organize. As a term of synergetic theory, fluctuations are defined as the deviation of parameters from the general trend. Special aggregates according to Commission Regulation (EC) No 251/2009 of 11.03.2009 by the level of technology use were the object of this study. The technological imbalance index of the national economy and Theil indices separately for manufacturing and services were calculated. Both indicators were based on the amount of added value per employee. The analysis of the dynamics of these indicators showed a high level of imbalance of the technological sphere in terms of employment efficiency. The analysis of the dynamics of these indicators showed a high level of imbalance in the technological sphere in terms of employment efficiency. Quantitative fluctuations with signs of cyclicity over a period of about three years were detected. Structural fluctuation is associated with the leadership of the service sector in the use of labor resources compared to the production sector. The detected fluctuations are characterized as a manifestation of the nonlinearity of the development of a complex open techno-system of the country. The conclusion is made about the role of digitalization of the economy as an attractor that determines the main goal of the system development for the long term. This attractor is able to "push" the transformation processes in the direction of increasing the cumulative effects of the interaction of system elements and strengthening its ability to self-organize. The system of economic policy measures, taking into account the target orientation of economic development towards digitalization was proposed. The author emphasizes the fact that digitalization provides many opportunities for both increasing employment level and improving the educational and qualification level of employees and developing a culture of communication between citizens, business and the state. The synergistic effects of digitalization in the field of employment are also manifested in the unification of IT competencies, unidirectionality of personal, collective, state, and public interests, and increased interaction between business entities.
Use of technologies in the economy of Ukraine: practical aspects of the theory of fluctuations
Keywords: технології; ефективність використання ресурсу праці, флуктуації.; флуктуації; technologies; the efficiency of labor resource use; fluctuations